The Effects of Intellectual Property on Financial Integration in the European Union and Moldova Republic - Emmanuel Obed DADZIE; Ionela Gabriela MATEI (Eastern European Journal of Regional Studies, 2021)
In order to encourage creative work and prevent possible abuses, the field of intellectual property must be well regulated; from a legislative point of view. This present era which is characterized by continuous technological progress is experiencing a boost in relevance of intellectual property; thereby becoming one of the key elements of industries. This has made players of markets to become aware of the need to ensure protection of intellectual property rights. Hence, financial integration is a key element which can be affected by intellectual property and the innovation process involved. This paper analyses the correlation between international financial integration and intellectual property. Also, the analysis focuses on European Union (EU) member countries and Moldova in assessing the effects of intellectual property and international financial integration. Fixed-effect panel estimation and the ordinary least squares model are used in the analysis.The analysis has been conducted over the last two decades to see the differences that intellectual property has had over financial integrationover periods of time that have had extremely different economic oscillations. The results of this research provide an update on the analysis effects of intellectual property on international financial integration and it shows a negative relationship between them. Hence, this depicts that when intellectual property is carefully considered by firms and governmental institutions, it can be a major source of revenue for the stakeholders and the economy at large.